Yolk-shell silicon-mesoporous carbon anode with compact solid electrolyte interphase film for superior lithium-ion batteries. (November 2015) - Yang, Jianping; Wang, Yun-Xiao; Chou, Shu-Lei; Zhang, Renyuan; Xu, Yanfei; Fan, Jianwei; Zhang, Wei-xian; Kun Liu, Hua; Zhao, Dongyuan; Xue Dou, Shi
Abstract: Silicon as an electrode suffers from short cycling life, as well as unsatisfactory rate-capability caused by the large volume expansion ( 400%) and the consequent structural degradation during lithiation/delithiation processes. Here, we have engineered unique void-containing mesoporous carbon-encapsulated commercial silicon nanoparticles (NPs) in yolk-shell structures. In this design, the silicon NPs yolk are wrapped into open and accessible mesoporous carbon shells, the void space between yolk and shell provides enough room for Si expansion, meanwhile, the porosity of carbon shell enables fast transport of Li + ions between electrolyte and silicon. Our ex-situ characterization clearly reveals for the first time that a favorable homogeneous and compact solid electrolyte interphase (SEI) film is formed along the mesoporous carbon shells. As a result, such yolk-shell Si@mesoporous-carbon nanoparticles with a large void exhibits long cycling stability (78.6% capacity retention as long as 400 cycles), and superior rate-capability (62.3% capacity retention at a very high current density of 8.4 A g −1 ). Graphical abstract: Si@mesoporous carbon yolk-shell nanoparticles : A superior Si-based anodes consisting of a commercial Si nanoparticles yolk, a special designed void-containing spaces and a compact SEI film formed mesoporous carbon shell was fabricated by controllable sol–gel and nanocasting method for long cycle stability and high rate-capability of lithium-ion batteries. Highlights: The special design of the void spaces (10 and 50 nm) optimize the cycling stability. Mesoporous carbon shells favor the formation of a homogeneous and compact SEI film. Yolk-shell Si@mC NPs exhibits long cycling stability and excellent rate-capability.